Quantitative Analysis of Protein Translocations by Microfluidic Total Internal Reflection Fluorescence Flow Cytometry - Wang, Jun (2010)
Protein translocation, or the change in a protein’s location between different subcellular compartments, is a critical process by which intracellular proteins carry out their cellular functions. Aberrant translocation events contribute to various diseases ranging from metabolic disorders to cancer. In this study, we demonstrate the use of a newly developed single-cell tool, microfluidic total internal reflection fluorescence flow cytometry (TIRF-FC), for detecting both cytosol to plasma membrane and cytosol to nucleus translocations using the tyrosine kinase Syk and the transcription factor NF-κB as models. This technique detects fluorescent molecules at the plasma membrane and in the membrane-proximal cytosol in single cells. We were able to record quantitatively changes in the fluorescence density in the evanescent field associated with these translocation processes for large cell populations with single cell resolution. We envision that TIRF-FC will provide a new approach to explore the molecular biology and clinical relevance of protein translocations.